A comparative study of the legal framework on children protection from online predators in Malaysia and the United States of America (USA) / Ahmad Azlan Azizan … [et al.] - Azizan, Ahmad Azlan; Raja Ezham, Raja Nurul Izzah; Abdullah, Siti Aminah; Musa@Mohamad, Nor Aslizan; Kamaludin, Muhammad Ainuddin (Faculty of Law, 2010)
The publicity about online predators that prey on naive children using trickery and violence is improper. Internet sex crimes involving adults and juveniles more often fit a model of statutory rape-adult offenders who meet, develop relationships with, and openly seduce underage teenagers-than a model of forcible sexual assault or pedophilic child molesting. This is a serious problem that requires approaches different from those in current prevention messages emphasizing parental control and the dangers of divulging personal information. Malaysia does have laws such as the Communication and Multimedia Act 1998, the Penal Code and other types of enforcement but not a specific law as with the United States of America (USA). Specific legislation to deal with the children protection against offences committed by the online predators is of utmost necessary due to the in comprehensiveness of the current laws in Malaysia. Apart from legislative measures, there are appropriate prevention strategies that target youths directly and acknowledge normal adolescents with awareness and avoidance skills while educating older youth about the pitfalls of sexual relationships with adults and their criminal nature. Particular attention should be paid to higher risk youths, especially those with history of sexual abuse, sexual orientation concerns, and patterns off and online risk taking